Narwhal and Jelly book. 06 : Narwhal's school of awesomeness - Clanton, Ben, 1988- (Clanton, Ben, 1988- Narwhal and Jelly book, 2021)
"Dive into four . . . stories about Narwhal and Jelly becoming substitute teachers! The two best friends come across an enthusiastic school of fish one morning. Unfortunately, Mr. Blowfish, their teacher, has come down with a cold, and class will have to be cancelled--until Professor Knowell (Narwhal) and Super Teacher (Jelly) volunteer to help out!"--Provided by publisher.